Narcotics Registration and Payment Information System at BNN City Banjarmasin Clinic - Fitria; Iryanie, Emy; Heldalina, Heldalina; Khalid, Anhar (MultiTech Publisher, 2024)
In the clinic, the BNN Banjarmasin urine testing service is still manual, especially the registration and payment. It takes a long time and leads to a stay in service. The method in this research is a case study. Then a web-based computerised system is built so that for self-filled data in registrations and transactions, there is no need to bother with handwriting, and documents will be automatically recorded on the system. The author recommends that businesses integrate applications that are designed into their operations because doing so would increase the efficiency of all business transactions and allow the agency and patients to directly benefit from the system.